Changes In Enso Sea Surface Temperatures Drive Climate Change - Brunt, William Albert Van (European Journal of Applied Sciences, 2024)
There are two fundamental aspects of climate change, global warming and the massively increasing incidence and intensity of catastrophic weather. It is shown that both are driven by the increasing global concentration of water vapor (△TPW) resulting from increasing Sea Surface Temperatures in the Eastern Equatorial Pacific El Niño-Southern Oscillation or ENSO region of the Pacific (ENSO SST). Physical principles to determine changes in the annual average global temperature (△TAvg) and concentration of water vapor (△TPW) as a function of the first derivative of the 12 month average, for the period commencing in August of the prior year, sea surface temperatures within the ENSO region (△ENSO SST5mo) are set out. The resulting temperature determinations are within 0.4% of the NOAA annual global Celsius temperature record and TPW within 0.9% of published results. The data and these principles show that since 1972 the 1 °C increase in TAvg and an 11% increase in TPW are the result of a 5% cumulative increase in the ENSO SST and the 360% increase in annual catastrophic weather events, 400% increase in severity and resulting 1,400% increase in devastation are the result of the 11% increase in TPW (130% increase in devastation for each 1% change in TPW). Far more importantly, the data show and the physics teach that if average global precipitation is increased sufficiently, by 0.2% in excess of evaporation, these climate changes are completely reversible.